Campus Online Food Ordering System Using Chatbot In Universiti Sains Islam Malaysia - Nur Ilyana Ismarau Tajuddin; Nor AziyatulIzni; Aeshah Mohd Ali; Nurfaradilla Haron; Nor Asiah Mahmood; Nurafifah Mohd Nor; Nurul Aimy Atiqah Abd Razak (HOMSON REUTERS Publons, 2024)
Non-Indexed Publication